Dinamika Studi Hadis di PTKIN: Perkembangan, Tantangan, dan Prospek Masa Depan - Haramain, Izzadheva Ratu (SHAHIH (Jurnal Ilmu Kewahyuan), 2025)
This article explores the development of Hadith studies within Indonesian State Islamic Higher Education Institutions (PTKIN). The discussion focuses on the institutions' vision, mission, curriculum, and scientific orientation. While Hadith studies at PTKIN have shown significant progress, they still face challenges—particularly in developing a knowledge framework that is responsive to global dynamics. Increasing international academic competition demands that Muslim scholars and communities respond swiftly and accurately to contemporary issues. This research employs a qualitative approach through library-based study. The findings highlight the urgent need to reconstruct institutional systems that are more adaptive and globally competitive in addressing current and future challenges.